Water supply - University of the West of England (New York: Insight Media (distributor), 1997)
This video discusses common water sources, treatment, distribution and domestic installations. It focuses on direct and indirect systems, service entry, pipework, valves, metering and storage systems
Title from container
DVD format
Keywords: Water supply; Groundwater; Water -- Purification; House construction